2022
DOI: 10.1111/ajae.12335
|View full text |Cite
|
Sign up to set email alerts
|

Trade uncorked: Genetic distance and taste‐related barriers in wine trade

Abstract: A nascent literature explores the impact of taste differences on trade. In gravity model estimations, the coefficient on geographic distance is large because it tends to capture such (usually unobservable) preference-related frictions. We examine this question in the context of French wine, that is, a cultural good characterized by a great variety of types (i.e. accommodating a large heterogeneity in wine tastes) and of quality levels (from cheap table wine to the finest grands crus). A series of gravity model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…The use of digital inputs can increase the quality of exported products that are less sensitive to trade costs. Indeed, the trade literature on quality sorting and trade patterns has demonstrated that high‐end products are less sensitive to geographical distance (Bargain et al, 2023; Fontagné & Hatte, 2013; Martin & Mayneris, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The use of digital inputs can increase the quality of exported products that are less sensitive to trade costs. Indeed, the trade literature on quality sorting and trade patterns has demonstrated that high‐end products are less sensitive to geographical distance (Bargain et al, 2023; Fontagné & Hatte, 2013; Martin & Mayneris, 2015).…”
Section: Discussionmentioning
confidence: 99%